Векторы экспрессии на основе промоторов генов РНО3 и РНО5 дрожжей Saccharomyces cerevisiae: конструирование, сравнительная оценка эффективности, использование для суперпродукции фосфорибозиламиноимидазол-карбоксилазы - Останин, К.В.; Смирнова, Т.М.; Мясников, А.Н.; Гедвилайте, Д.А.; Саснаускас, К.В.; Смирнов, М.Н. (Биополимеры и клетка, 1988)
Сконструирован ряд дрожжевых векторов экспрессии на основе промоторов РНО3 и РНО5 дрожжей Saccharomyces cerevisiae, отличающихся положением делеции в промоторной области. Два из них испольованы для экспрессии дрожжевого гена ADE2. В результате получены штаммы дрожжей, у которых удельная активность продукта ADE2—фосфорибозиламиноимидазол-карбоксилазы приблизительно в 1000 раз выше, чем у штаммад дикого типа. Сконструйовано низку дріжджових векторів експресії на основі промоторів РНО3 і РНО5 дріжджів Saccharomyces cerevisiae, що відрізняються за положенням делеції у промоторній області. Два з них використано для експресії дріжджового гена ADE2. У результаті отримано штами дріжджів, у яких питома активність продукту ADE2-фосфорибозиламіноімідазол-карбоксилази приблизно в 1000 разів вища, ніж у штаму дикого типу. A series of yeast expression vectors based on promoters of PHO3 and PHO5 genes and transcription terminator region of the PHO5 gene have been constructed. One of the vectors incorporates the site of PHO5 coding for the structure of the leader peptide. The promoter region of these expression vectors is flanked by a fragment of the pUC19 polylinker containing unique restriction sites for EcoRI, Sad, Kpnl and Smal. The efficiency of these vectors was tested in a model study in which they have been used to overproduce the product of yeast ADE2 gene — aminoimidasole carboxylase. The specific activity of this enzyme in yeast transformants was about 1000 times higher than in wild type yeast strains.